Putting All Your Eggs in One Basket - White, Andrew Edward; Li, Yexin Jessica; Griskevicius, Vladas; Neuberg, Steven L.; Kenrick, Douglas T. (Psychological Science, 2013)
Diversification of resources is a strategy found everywhere from the level of microorganisms to that of giant Wall Street investment firms. We examine the functional nature of diversification using life-history theory—a framework for understanding how organisms navigate resource-allocation trade-offs. This framework suggests that diversification may be adaptive or maladaptive depending on one’s life-history strategy and that these differences should be observed under conditions of threat. In three studies, we found that cues of mortality threat interact with one index of life-history strategy, childhood socioeconomic status (SES), to affect diversification. Among those from low-SES backgrounds, mortality threat increased preferences for diversification. However, among those from high-SES backgrounds, mortality threat had the opposite effect, inclining people to put all their eggs in one basket. The same interaction pattern emerged with a potential biomarker of life-history strategy, oxidative stress. These findings highlight when, and for whom, different diversification strategies can be advantageous.